Pengaruh Edukasi Manajemen Laktasi Terhadap Motivasi dan Kesiapan Ibu dalam Pemberian Asi Eksklusif di Rumah Sakit Panti Waluyo Surakarta - Dian Sekarsari; Heny Purwaningsih; Tria Puspita Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Breast milk is ideal nutrition for babies which contains nutrients and a set of protective substances to fight disease. Lactation education is a learning process to prepare oneself psychologically and physically to be able to breastfeed exclusively. Based on observations and interviews of third trimester pregnant women at Panti Waluyo Hospital from February to April 2023, 289 mothers had not received information about lactation education. Objective: To determine the effect of lactation management education on mothers' motivation and readiness to provide exclusive breastfeeding. Design: This type of research is a one group pre-post test design with pre and post experimental. This research was conducted at Panti Waluyo Hospital in August – December 2023. The research instruments used educational videos, pre and post questionnaires. Data analysis used the Shapiro Wilk test, Oneway Anova test, and Paired T Test. Results: Most of the respondents were aged 17-25 years as many as 32 respondents, the last level of education was DIII was 20 respondents, parity had never given birth as many as 20 respondents and history of childbirth had never given birth as many as 22 respondents. There are differences in mothers' motivation and readiness before and after being given lactation management education as shown by a p value of 0.044. Data on mothers' motivation and readiness before and after being given lactation management education varied the same as shown by p values of 0.199 and 0.499. There is an influence of lactation management education on mothers' motivation and readiness to provide exclusive breastfeeding, shown by a p value of 0.001. Conclusion: there is an influence of lactation management education on mothers' motivation and readiness to provide exclusive breastfeeding.